Case report: From palliative to potentially curative – the advent of immunotherapy providing hope to advanced gallbladder adenocarcinoma - Leong, Eugene Kwong Fei; Tan, Nigel Chun Hian; Pang, Ning Qi; Kow, Alfred Wei Chieh (Frontiers in Immunology, 2024)
Introduction Biliary tract cancers (BTC) are often diagnosed at an advanced stage where prognosis is poor and curative-intent surgery is infeasible. First-line cisplatin-gemcitabine chemotherapy for advanced gallbladder cancer has remained unchanged over more than a decade, but recent developments in immunotherapy such as durvalumab have highlighted promise as a combination treatment regime with current standard chemotherapy. Methods In this case description, we present a case of locally-advanced gallbladder adenocarcinoma involving the biliary confluence that was initially planned for an extended right hepatectomy after portal vein embolization. Interval imaging revealed peritoneal metastasis, which was confirmed on diagnostic laparoscopy and biopsy. The patient underwent 8 cycles of cisplatin 25 mg/m2 and gemcitabine 1,000 mg/m2 chemotherapy on days 1 and 8 of each 21-day cycle, with durvalumab (Imfinzi®) 1,500 mg immunotherapy on day 1 of every cycle, in accordance with the treatment protocol of the TOPAZ-1 trial. Repeat imaging demonstrated a stable primary lesion with no further evidence of peritoneal disease. The patient subsequently underwent curative-intent conversion surgery with an extended right hepatectomy and Roux-en-Y hepaticojejunostomy, which were completed through a fully minimally-invasive laparoscopic approach. Results Final pathological TNM classification was ypT1aN0, with near-complete pathological response to pre-surgical therapy, uninvolved margins (R0 resection) and tumour shrinkage from 2.5 centimetres on pre-operative cross-sectional imaging to 0.5 centimetres on final histology. The patient had an uneventful post-operative course, and was fit for discharge by the fourth post-operative day. He remained well after three months of routine post-operative follow-up, with no significant post-operative complications and biochemical or radiological evidence of disease recurrence. Conclusion Our case description highlights the immense potential of combination durvalumab immunotherapy with cisplatin-gemcitabine chemotherapy in the treatment of advanced gallbladder adenocarcinoma. The patient’s locally advanced disease was initially planned for complex open surgery, prior to discovery of peritoneal metastasis rendering it inoperable. This was successfully down-staged with combination therapy to eventual R0 resection via minimally-invasive surgery. In addition, this case description demonstrates the feasibility of a fully laparoscopic approach with postulated benefits of diagnostic re-evaluation of peritoneal disease, reduced wound pain and shorter length of hospital stay.